2023
DOI: 10.1200/op.23.00007
|View full text |Cite
|
Sign up to set email alerts
|

Pretest Video Education Versus Genetic Counseling for Patients With Prostate Cancer: ProGen, A Multisite Randomized Controlled Trial

Huma Q. Rana,
Jill E. Stopfer,
Michelle Weitz
et al.

Abstract: In this large, multisite RCT, pretest video education shows promise for men with prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Therefore, alternate delivery models for genetics care delivery are needed. The ProGEN randomized clinical trial showed no differences in uptake and completion of genetic testing interventions between video‐based and in‐person genetic counseling, 61 the EMPOWER study showed males prefer pre‐test video based counseling, 62 and the GENTleMEN study showed high genetic testing rates using internet‐based testing platforms 63 . Despite these successes, low rates of genetic testing uptake remain in self‐identified Black and Asian populations, and additional efforts are needed to increase genetic testing rates in these populations.…”
Section: Reducing Prostate Cancer Morbidity and Mortality With Geneticsmentioning
confidence: 99%
“…Therefore, alternate delivery models for genetics care delivery are needed. The ProGEN randomized clinical trial showed no differences in uptake and completion of genetic testing interventions between video‐based and in‐person genetic counseling, 61 the EMPOWER study showed males prefer pre‐test video based counseling, 62 and the GENTleMEN study showed high genetic testing rates using internet‐based testing platforms 63 . Despite these successes, low rates of genetic testing uptake remain in self‐identified Black and Asian populations, and additional efforts are needed to increase genetic testing rates in these populations.…”
Section: Reducing Prostate Cancer Morbidity and Mortality With Geneticsmentioning
confidence: 99%